Development and validation of a QbD-based RP-HPLC method for vericiguat quantification - Mandhare, Shubham; Godge, Rahul; Vikhe, Akshay; Talole, Shubham (Journal of Applied Pharmaceutical Research, 2024)
Aim: An RP-HPLC method for Vericiguat using the QbD approach was developed and validated by ICH guidelines. Method: The ICH (Q2R1) guidelines have been followed in the development and validation of an RP-HPLC technique by considering several validation parameters like linearity, precision, LOD, LOQ, and accuracy. The study was performed on Agilent Tech using the C18 column (4.6x250 mm; 5 µm) and Chemstation 10.1 software with statistical data analysis, and the detector used was UV (DAD). Results: The mobile phase used for separation was Methanol: 0.1% OPA in the ratio of (76:24) at room temperature, the flow rate was 0.8ml/min, and the wavelength was 331nm. The results indicated that the quantification limit was 0.7209 µg/ml, and the detection limit was 0.2379 µg/ml. Conclusion: The validation studies confirmed that the developed method is fast, accurate, precise, cost-effective, selective, and useful for routine analysis of vericiguat in tablet dosage forms.